Temperature Characteristics of Pine Stems in the Northern Taiga Subzone - Pavel A. Feklistov; Ekaterina A. Pinaevskaya; Nikolay A. Neverov; Ivan N. Bolotov; Sergei N. Tarkhanov; Olga N. Tyukavina (Лесной журнал)
The research has been carried out in the northern taiga in pine forests of different types in the Novodvinsk and Isakogorka forestries of the Arkhangelsk forestry district. All the studied pine forests are characterized as middle-aged, pure in composition or with a small admixture of spruce and birch. The aim of the research has been to determine the temperature of the internal tissues of the xylem, since despite the fact that woody plants are poikilothermic organisms, their temperature differs from that of the air. In each forest type, 45–50 registered trees have been selected for the study. To measure the temperature of the bark surface, a Testo 890-2 thermal imager has been used, meteorological factors near the trees have been determined using a MES-200 device, and the xylem temperature has been determined using a portable digital multimeter MY 64. It has been shown that the surface temperature of the stems and the xylem temperature differ significantly from the ambient air temperature. The temperature of the smooth bark in warm weather has turned out to be lower than the temperature of the crust (fissured bark) by 2 °С, or by 10 %. Thin trees have a crust temperature higher than thick trees by 1.5 °С, or 7 %. In sunny, cloudless weather, the bark surface temperature in blueberry and shrubby-sphagnum pine forests is higher than the air temperature: by 0.98 °С in blueberry pine forests and by 5.43 °С in shrubby-sphagnum pine forests. In cloudy weather, on the contrary, the air temperature exceeds the temperature of the surface of the needles. The xylem temperature at the root collar is always lower than at a height of 1.3 m. The differences are from 0.8 to 1.2 °С. Apparently, this is due to the temperature of the water that flows from the soil into the xylem. The xylem temperature increases during the growing season and reaches a maximum by the end of July, after which it decreases. The xylem temperature is always lower than the air temperature and depends on the age – in older trees the indicator is lower.